A modified NSGA-II solution for a new multi-objective hub maximal covering problem under uncertain shipments - Amir Ebrahimi Zade; Ahmad Sadegheih; Mohammad Mehdi Lotfi (Journal of Industrial Engineering International, 2014)
Hubs are centers for collection, rearrangement,and redistribution of commodities in transportation networks. In this paper, non-linear multi-objective formulations for single and multiple allocation hub maximal covering problems as well as the linearized versions are proposed. The formulations substantially mitigate complexity of the existing models due to the fewer number of constraints and variables. Also, uncertain shipments are studied in the context of hub maximal covering problems. In many real-world applications, any link on the path from origin to destination may fail to work due to disruption. Therefore, in the proposed bi-objective model, maximizing safety of the weakest path in the network is considered as the second objective together with the traditional maximum coverage goal. Furthermore, to solve the bi-objective model, a modified version of NSGA-II with a new dynamic immigration operator is developed in which the accurate number of immigrants depends on the results of the other two common NSGA-II operators, i.e. mutation and crossover. Besides validating proposed models, computational results confirm a better performance of modified NSGA-II versus traditional one.
Keywords: 650; Facility location; Mathematical modeling; Hub maximal covering; Uncertainty; NSGA-II; Immigration operator